Implementasi Metode Snowball Throwing pada Pembelajaran Pendidikan Agama Islam - Riski, Arina; Siregar, Nurul Qolbiah; Midun, Midun; Sahara, Afni; Halimah, Nur (An-Nuha, 2022)
Education is a conscious and planned effort in the learning process to enable students to develop into individuals who are independent, responsible, creative, knowledgeable, healthy, and possess noble character. In the learning process, the Islamic Education (PAI) teacher implemented the Snowball Throwing method to encourage students to think more creatively and to create a more enjoyable learning atmosphere. This study employed a qualitative research method with a field research approach. The data sources for this research were the Islamic Education teacher and the eighth-grade students. Data collection techniques included observation, interviews, and documentation. The data analysis techniques consisted of data reduction, data display, and drawing conclusions. The results of this study indicate that the implementation of the Snowball Throwing method in PAI learning for class VIII at SMPN 5 Panyabungan has been successfully carried out. This is evident from the highly appropriate execution of the Snowball Throwing method in PAI lessons, where teachers and students interact with one another. This interaction is aimed at overcoming student boredom, fostering creative thinking, training leadership potential in learning PAI, and achieving academic success in the subject. The implementation steps taken by the Islamic Education teacher in the Snowball Throwing method are: the teacher explains the material first, then forms groups; subsequently, students write questions on a piece of paper shaped into a ball and throw it to another group, which then answers the questions received.